(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This article provides an outline of the mobile communications industry’s evolution. Even though there are various systems that are not interoperable, 2G technologies have had a huge uptake. Although 3G will offer some convergence, it will fall short of the goal of creating a unified worldwide technology. IP is becoming more significant at the network level. WLAN is delivering a supplementary technology to cellular in hot spot environments.